A concurrent dual-band CMOS low noise amplifier at 2.4/5.2 GHz for WLAN applications - S.A.Z. Murad; A. F. Hasan; A. Azizan; A. Harun; J. Karim (Indonesian Journal of Electrical Engineering and Computer Science, 2019)
This paper presents a concurrent dual-band CMOS low noise amplifier (LNA) at operating frequency of 2.4 GHz and 5.2 GHz for WLAN applications. The proposed LNA employed cascode common source to obtain high gain using 0.13-µm CMOS technology. The concurrent dual-band frequencies are matched using LC network band-pass and band-stop notch filter at the input and output stages. The filters help to shape the frequency response of the proposed LNA. The simulation results indicate that the LNA achieves a forward gain of 21.8 dB and 14.22 dB, input return loss of -18 dB and -14 dB at 2.4 GHz and 5.2 GHz, respectively. The noise figure of 4.1 dB and 3.5 dB with the input third-order intercept points 7 dBm and 10 dBm are obtained at 2.4 GHz and 5.2 GHz, respectively. The LNA dissipates 2.4 mW power at 1.2 V supply voltage with a chip size of 1.69 mm2.